JESD 2019
DOI: 10.7176/jesd/10-18-18
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Exchange Rate and Economic Growth Nexus: New Evidence from Nigeria (1981 to 2017)

Abstract: The paper estimates the impact of foreign exchange rate on economic growth of Nigeria. The study makes used of Autoregressive Distributed Lag model (ARDL) on time series Data, for the period 1981-2017. The data set on real effective exchange rate, inflation rate, money supply, lending interest rate, real GDP and foreign direct investment, oil revenue and trade openness (% of GDP) were tested for stationary using ADF and PP tests and established stationarity at I (1) for five variables and I (0) for two variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…However, Economic performance of the manufacturing sector responded negatively and significantly to Naira/Pound Sterling exchange rate fluctuations (meaning, changes in Naira value against Pound Sterling) for the considered sample period. These findings corroborate the work of previous researchers (Oseni, 2016;Alagidede& Ibrahim, 2017;Ufoeze, et al, 2018;Amoah &Ahiabor, 2019;Musa, et al, 2019;Ribeiro, et al, 2020;Alasha, 2020;Onwuka, et al, 2020;Iheanachor&Ozegbe, 2021;Elijah, et al, 2022;Ewubare&Ushie, 2022) who found that a fluctuation of the Naira to foreign currency has a negative impact on the performance of the Nigerian economy. Meanwhile, the third hypothesis found that Foreign exchange supply on the contrary led to a positive impact on the economic performance of the manufacturing sector but does not significantly have effect on the economic performance of manufacturing sector for the sample period being considered.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…However, Economic performance of the manufacturing sector responded negatively and significantly to Naira/Pound Sterling exchange rate fluctuations (meaning, changes in Naira value against Pound Sterling) for the considered sample period. These findings corroborate the work of previous researchers (Oseni, 2016;Alagidede& Ibrahim, 2017;Ufoeze, et al, 2018;Amoah &Ahiabor, 2019;Musa, et al, 2019;Ribeiro, et al, 2020;Alasha, 2020;Onwuka, et al, 2020;Iheanachor&Ozegbe, 2021;Elijah, et al, 2022;Ewubare&Ushie, 2022) who found that a fluctuation of the Naira to foreign currency has a negative impact on the performance of the Nigerian economy. Meanwhile, the third hypothesis found that Foreign exchange supply on the contrary led to a positive impact on the economic performance of the manufacturing sector but does not significantly have effect on the economic performance of manufacturing sector for the sample period being considered.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…Ewubare and Ushie ( 2022) noted that exchange rate has direct impact on macroeconomic variables therefore plays a vital role of growth in nations building. However, reliance on importation for capital goods and finished goods, unexampled reduction in utilization rate in trade in addition to diverted attention from agricultural sector are responsible for low incomes and debased living standards of Nigerians (Musa, Muhammad, Mohammed &Adamu, 2019). The implications and consequences of fluctuation in exchange rate, on the macroeconomics of developing nations like Nigeria has been a great concern (Iheanachor&Ozegbe 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in theory, if the right regime is adopted, it could facilitate better business climate and potentially enhance economic growth in the long-run. Economic theory does not clearly articulate how exchange rate regimes can affect economic growth, and there are a limited number of studies which investigate this relationship (Musa et al, 2019) [15,16] . i).…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…In portfolio analysis, the current account balance becomes the reflection of the government budgetary imbalance when the private sector is satisfied with the holding of financial assets. The inability of government to sell bonds to foreigners without an excessive fall in their prices reflected in the overall balance of payment deficit Musa et al (2019) [15,16] . ii).…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation